A comparison of service efficiency between players of male and female doubles at professional tennis tournaments - Carboch, J.; Kocíb, T. (AUC Kinanthropologica, 2015)
Male and female players have a different quality of service. For example, men can reach a higher service speed, or use more ball spin. Tennis service has also a different efficiency on different surfaces. Every surface has specific characteristics and has different effects on ball impact and ball bounce. The aim of our study was to compare the amount of service points won between male and female players in men`s and women`s doubles at ATP (Association of Tennis Professionals) and WTA (Women Tennis Association) tournaments on three different surfaces. We observed a total of 303 matches. Matches were played on clay, hard and grass courts. With the help of match records, we found that men won around 10% service points more than women. Results indicate that women`s doubles matches show greater differences in performance between opponents. Men also need to win more service points than women, to win a match. Fast surfaces provide a greater advantage for serving teams, both for men and women. The lowest serve efficiency was reached on clay (slow surface) both in the men`s and women`s doubles.